Karakteristik Pekerjaan Utama terhadap Sektor Informal dan Sektor Formal di Provinsi Gorontalo - Mahmud, Sri Ayu I; Saleh, Sri Endang; Payu, Boby Rantow (Economic Reviews Journal, 2024)
This study aims to analyze (i) the magnitude of the influence of working hours on labor income (ii) the magnitude of the influence of employment status on labor (iii) the magnitude of the influence of training on labor income (iv) the magnitude of the influence of training/courses on data Labor income used in this research is secondary data sourced from the Central Statistics Agency obtained from the National Labor Force Survey. This research uses Multinomial Logistic Regression Analysis. The results of this research show that the influence of main work with indicators of working hours, employment status, training certificates, and training/courses has a positive and significant influence on the income of workers in the informal and formal sectors, meaning that every 1 percent increase in main workers can increase the income of workers in the informal and formal sectors. Formal in Gorontalo Province.